Konica v vrstičnem tunelskem mikroskopu - Florjančič, David (Matrika, 2016)
This article is about the preparation of tips for scanning tunneling microscope (STM). With the STM the tunneling current between the STM tip and sample is measured. The tip must have appropriate physical and chemical properties to be used in the STM. The process of preparation platinum/iridium and tungsten tips is described. It is also explained how the quality of the tip can be improved in the vacuum system.
Keywords: microscope tip; preparation; priprava konice; scanning tunneling microscope; tunelski tok; tunneling current; vrstični tunelski mikroskop